Integrating serum pharmacochemistry and network pharmacology to reveal the active constituents and mechanism of Corydalis Rhizoma in treating Alzheimer’s disease - Lyu, Yan; Wang, Yu; Guo, Jianyou; Wang, Yuqing; Lu, Yifan; Hao, Zhuangzhuang; Jiang, Tingyue; Fan, Wenxin; Li, Yihua; Shi, Jinli (Frontiers in Aging Neuroscience, 2023)
Background: Alzheimer's disease (AD) is a multifactorial neurodegenerative condition. The search for multi-target traditional Chinese medicines or ingredients for treating AD has attracted much attention. Corydalis rhizome (CR) is a traditional Chinese medicine. Its main components are alkaloids, which have therapeutic effects that can potentially be used for treating AD. However, no systematic study has been conducted to explore the anti-AD efficacy of CR, as well as its active compounds and mechanisms of action.Objective: The present study aimed to clarify CR's active constituents and its pharmacological mechanisms in treating AD.Methods: A D-galactose & scopolamine hydrobromide-induced AD mouse model was used and CR was administered orally. The prototypical alkaloid components were identified in the serum. The core components, key targets, and possible mechanisms of action of these alkaloids were revealed through network pharmacology. Molecular docking of the key target was performed. Finally, the mechanism was validated by lipopolysaccharide (LPS)-induced activation of BV2 microglia.The results showed that CR improved anxiety-like behavior, spatial and non-spatial recognition, and memory capacity in AD mice. It also achieved synergistic AD treatment by modulating neurotransmitter levels, anti-neuroinflammation, and anti-oxidative stress. The core components that enhance CR's efficacy in treating AD are protoberberine-type alkaloids. The CR may induce the polarization of LPS-activated BV2 microglia from phenotype M1 to M2. This is partially achieved by modulating the IL-6/JAK2/STAT3 signaling pathway, which could be the mechanism by which CR treats AD through anti-inflammation. This is a provisional file, not the final typeset articleThe present study provided a theoretical and experimental basis for the clinical application of CR in treating AD. It also provides information that aids the secondary development, and precise clinical use of CR.